Terites, Kuliner Ekstrim Khas Karo Sebagai Daya Tarik Wisata Kuliner - Mulya Sari Hadiati; Muhamad Mirum Sapat Surbakti (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2021)
The Batak tribe, which is divided into several tribes, is the majority population domiciled in North Sumatra Province. Including the Karo Tribe, who mostly live in Tanah Tinggi Karo. The Batak people still carry out their ancestral cultural traditions. In traditional ceremonies of the Karo Tribe, food is an important part. There are foods that are only available at traditional ceremonies. Karo's typical cuisine is unique in terms of the use of ingredients, it can even be said to be extreme. One of them is terites, grass contained in the stomach of cows. Terites already qualifies as a culinary tourism attraction, but the taste is bizare. This is the problem in this study. The purpose of this research is to find out whether terites as extreme culinary can be accepted by the tastes of the non-Karo people. This scientific writing uses the journal review method, namely reviewing several previous journals, theses and hedonic test. To find out the level of preference of non-Karo people towards terites, a hedonic test was carried out on four trained panelists who live in Jakarta. Hedonic test results: taste, appearance, and texture are acceptable. However, a scent that too pungent is unacceptable.